Millennial Multiliteracy Genre Handbook Model to Improve English Student’s Achievement - Rudi Permadi (Universitas Majalengka, 2021)
It focusses on improving student’s English achievement assisted by media namely millennial multiliteracy genre handbook model. It plays research and development model consisting of 6 stages, as follows (1) preliminary study; (2) research planning; (3) product design; (4) product validation; (5) product trials carried out at three stages of the individual, small, and limited scaled and; (6) the final product. Three different colleges (STAI Tasikmalaya, LP3I Tasikmalaya and Politeknik Triguna Tasikmalaya) becomes the places obtaining the data. The media validation result by the book expert obtained 84.6% and by the material expert resulted 85.3%. The developed media was valid and did not need any revision. The research finds that the total students’ respond on individual scale is 81 %, the total students’ respond on small scale is 79 %, and the total students’ respond on limited scale is 82%. It indicates that millennial multiliteracy genre handbook model strongly valid and it can be used as media to teach English at colleges or universities level. Furthermore, millennial multiliteracy genre handbook model gives positive contribution on the students’ English learning achievement because the significant level is 0.000 less than 0.5.